The salutary effect of peritoneal dialysis catheters on enhanced recovery among high-risk pediatric patients undergoing the left coronary transfer procedure: a cohort study - Chunrong Wang; Yuefu Wang; Fuxia Yan; Peng Fu; Jun Li; Lijing Yang; Sheng Shi; Jianhui Wang; Yuchen Gao; Sudena Wang; Yu Tian (BMC, 2021)
Abstract Background Evidence for peritoneal dialysis catheter (PDC) usage in pediatric patients undergoing surgery for deteriorating cardiac dysfunction is lacking. This investigation explored factors associated with PDC usage and its effectiveness in children with anomalous origin of the left coronary artery from the pulmonary artery (ALCAPA). Methods Eighty-four children undergoing left coronary artery transfer were retrospectively recruited. The primary endpoint was the postoperative ratio of the general ward/[intensive care unit (ICU)] length of stay. Univariable and multivariable analyses were fitted to assess factors related most strongly to PDC and the ratio of general ward/ICU length of stay. Results Of the 84 patients, 17 (20.2%) underwent postoperative PDC placement. Patients with extreme cardiac dysfunction [left ventricular ejection fraction (LVEF) ≤25%] were much more likely to require a PDC (OR, 9.88; 95% CI, 2.13-45.76; P = 0.003). Moreover, univariate analysis indicated that concomitant mitral repair significantly decreased the likelihood of PDC placement (OR, 0.25; 95% CI, 0.07-0.85; P = 0.026). In those with cardiac dysfunction (LVEF ≤50%), PDC use was associated with a reduced ratio of ward/ICU length of stay (B, − 1.62; 95% CI, − 2.77- -0.46; P = 0.008), as was age ≤ 12 months (B, − 1.57; 95% CI, − 2.88- -0.26; P = 0.02). At the 1-year follow-up, cardiac improvement was significantly greater in patients with PDC usage than in those without it (P <  0.001), and the number of mitral recoveries was comparable between the groups (64.2% vs. 53.3%, P = 0.434). Conclusion In cohorts with ALCAPA, PDC placement following surgery may be necessary for patients with extreme cardiac compromise, while concomitant mitral repair can probably reduce their usage rate. PDC is beneficial in conferring an improvement in cardiac and mitral performance. Importantly, after patients are transferred from the ICU, recovery efficiency in the general ward can be enhanced by PDC placement, and hospital discharge can therefore be achieved early, especially for patients younger than 12 months or with LVEF ≤50%.